Substitution of Foreign Prescribed Medicines by Community Pharmacies in Palestine: A Legal and Pharmaco-Economic Analysis - Waleed M. Sweileh (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
The purpose of this study was to asses the rate and the trend of foreign drug substitution by community pharmacies in Palestine, and to analyze the legal issues influencing prescription substitution such as physicians' acceptance. The study was made on a randomly selected list of foreign drugs. A total of 1425 prescriptions from twenty community pharmacies were analyzed for foreign drug substitution. The substitution rate was 25.8%. More than 58% of these substitutions were agreed by the prescribing physician. The most commonly substituted drugs were those that have a price difference compared with the local product equivalents. This study shows that foreign drug substitution in Palestine is common and mostly encouraged by patients to reduce prescription costs. This study also, shows that there is a need to modify the existing pharmacy practice law regarding brand name substitution.